Impact of different cropping conditions and tillage practices on the soil fungal abundance of a Phaeozem luvico - Díaz Gómez, Andrea Romina (2015)
Fungal diversity seems to be a good indicator of ecosystem disturbance and functioning. The purpose of this work was to quantify the fungal population as a sensitive indicator of the changes caused by stubble placement in two tillage systems: reduced tillage (RT) and conventional tillage (CT) with and without cropping. To this end, we determined the effect of soil disturbances such as N fertilization, tillage practice, and cropped area on the soil fungal communities of a Phaeozem luvico of the El Salado river basin (Argentina). Soil samples (at 0-10 cm depth) were collected from a field cultivated with wheat at post-harvest, before sowing and at tillering. The relative abundance of individuals of the fungal population was studied on Nash Snyder and Oxgall agar media after different treatments and assessed as colony forming units (CFU/g of soil). The diversity of the fungal population was studied by Shannon´s index (H). The tillage system showed a marked effect only at post-harvest and the number of propagules was highest under RT for both culture media. The largest values of H were found only at post-harvest when Oxgall agar was used. A significant decrease in the values of H was observed when CT and high fertilization was applied in the wheat cropped area. The relative abundance of individuals of the fungal population was different in soils under the different tillage practices.